Distribuição diária das atividades comportamentais dos camarões marinhos Farfantepenaeus subtilis (Pérez Farfante, 1967) e Litopenaeus schmitti (Burkenroad, 1938) em condições laboratoriais - Medeiros, Melquieges Sousa de (2008)
Marine aquaculture has developed in the last decades all over the world, especially related to shrimp management. In Brazil, the introduction of the species Litopenaeus vannamei has contributed to the success of the activity, even if there are problems associated with the management of a exotic species, such as new diseases and ecological pressure on native species. It has been emphasized the need of research for developing new methodology that will allow native species management, being the most important Farfantepenaeus subtilis and Litopenaeus schmitti. Most knowledge obtained from research with those species has generally used a technical approach and mainly focused feeding process. There are no specific behavioral data on their activity pattern which should be of great importance for the use of native species on commercial culture farms. So, it was our objective to study and compare the daily distribution of behavioral activities of the marine shrimp species Litopenaeus schmitti and Farfantepenaeus subtilis. Forty animals of each species, 5 individuals per aquarium, were maintained in aquaria containing 200L of sea water under continuous aeration and filtration. They were marked individually and were observed by the instantaneous focal time sampling, along 10 continuous days, in 6 daily 15 min observation windows, every two hour. In each window, behaviors and location position of the animals in the aquarium were registered at 1 min intervals. Food was offered 3 times a day, representing 10% of each aquarium biomass. Aquaria were maintained in artificial photoperiod, 12hour light/l2 hour dark, 4 aquaria in light cycle equivalent to the environmental one (light from 06:00 to 17:59 h and dark from 18:00 to 05:59 h) and the other 4 in the reverse light cycle (light from 18:00 to 05:59 h and dark from 06:00 to 17:59 h) to allow sequential behavioral observation in both phases of the 24 hour cycle. There was a clear distinction between the distribution of behavioral activities of F. subtilis and L. schmitti in the two phases. The activity pattern of Farfantepenaeus subtilis demonstrates that species has prominently night habits and a burying pattern during the light cycle. Exploration, inactivity and swimming were the most common activities. The behavioral pattern of Litopenaeus schmitti indicates that species is active along both phases of the light cycle, and the most evident behaviors were exploration, inactivity and swimming